Proteolytic cleavage of the urokinase receptor substitutes for the agonist-induced chemotactic effect. - Resnati, M (1996)
Physiological concentrations of urokinase plasminogen activator (uPA) stimulated a chemotactic response in human monocytic THP-1 through binding to the urokinase receptor (uPAR). The effect did not require the protease moiety of uPA, as stimulation was achieved also with the N-terminal fragment (ATF), while the 33 kDa low molecular weight uPA was ineffective. Co-immunoprecipitation experiments showed association of uPAR with intracellular kinase(s), as demonstrated by in vitro kinase assays. Use of specific antibodies identified p56/p59hck as a kinase associated with uPAR in THP-1 cell extracts. Upon addition of ATF, p56/p59hck activity was stimulated within 2 min and returned to normal after 30 min. Since uPAR lacks an intracellular domain capable of interacting with intracellular kinase, activation of p56/p59hck must require a transmembrane adaptor. Evidence for this was strongly supported by the finding that a soluble form of uPAR (suPAR) was capable of inducing chemotaxis not only in THP-1 cells but also in cells lacking endogenous uPAR (IC50, 5 pM). However, activity of suPAR require chymotrypsin cleavage between the N-terminal domain D1 and D2 + D3. Chymotrypsin-cleaved suPAR also induced activation of p56/p59hck in THP-1 cells, with a time course comparable with ATF. Our data show that uPA-induced signal transduction takes place via uPAR, involves activation of intracellular tyrosine kinase(s) and requires an as yet undefined adaptor capable of connecting the extracellular ligand binding uPAR to intracellular transducer(s).